Estimating the Knowledge Capital Model for Foreign Investment in Services: The Case of Singapore - Gnanaraj Chellaraj; Aaditya Mattoo (East Asian Economic Review (EAER), 2019)
Singapore's inward and outward investments with industrialized countries in both manufacturing and service sectors were skill seeking while outward investments to developing countries were labor seeking. Applying the Knowledge-Capital model, it was found that services Foreign Direct Investment is sensitive to skill differences. A tenpercent decline in skill differences with industrialized countries resulted in a 4.25 percent rise in inbound manufacturing and 1.48 percent rise in inbound services investments. Meanwhile, a ten-percent increase in skill differences with developing countries resulted in a 30 percent rise in outbound manufacturing and 0.38 percent rise in services investments. Furthermore, when services are distinguished by skill-intensity, the impact of relative skill endowments on inbound Foreign Direct Investment in skill-intensive services is significantly different from the impact on other services. However, when services are disaggregated by "proximity" needs, we do not find any significant difference in the impact of relative skill endowments on Foreign Direct Investment.
Keywords: F00; F21; I25; 330; Foreign Direct Investment; Manufacturing; Services; Skills; Proximity